Dairy Business Analysis Project: 2005 Financial Summary - Russell Giesy; Lane Ely; Brent Broaddus; Chris Vann; A. Bell; Albert De Vries (EDIS, 2007)
AN179, an 18-page publication by R. Giesy, L. Ely, B. Broaddus, C. Vann, A. Bell, and A. De Vries, is a summary of the financial performance of the dairy farms that participated in 2005. It is intended for general use by dairy farmers, the allied industry, and government and educational professionals. Published by the UF Department of Animal Sciences, February 2007.